Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1242/jcs.200493
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin 1 binds PDGF-D and is a co-receptor in PDGF-D–PDGFRβ signaling

Abstract: Platelet-derived growth factor (PDGF)-D is a PDGF receptor β (PDGFRβ)-specific ligand implicated in a number of pathological conditions, such as cardiovascular disease and cancer, but its biological function remains incompletely understood. In this study, we demonstrate that PDGF-D binds directly to neuropilin 1 (NRP1), in a manner that requires the PDGF-D C-terminal Arg residue. Stimulation with PDGF-D, but not PDGF-B, induced PDGFRβ-NRP1 complex formation in fibroblasts. Additionally, PDGF-D induced transloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 48 publications
1
47
0
Order By: Relevance
“…Similar to the involvement of Semaphorin ligands, the possibility remains that NRP TM dimerization is not required but may somehow modulate HH signaling. It is also possible that NRP interactions with other TM proteins, such as VEGF receptors, Plexins, FGF receptors, or PDGF receptors, may contribute to HH signal promotion (67,81), although many of these receptors interact with NRP1 through its extracellular domain, which, as our data indicate, is dispensable for NRP1 function in HH signaling. This contrasts with the extracellular domain, which is required for Semaphorin signaling, and a conserved SEA motif that is required for VEGF signaling.…”
Section: Identification Of a Cytoplasmic Motif In Nrp1 That Mediates mentioning
confidence: 75%
“…Similar to the involvement of Semaphorin ligands, the possibility remains that NRP TM dimerization is not required but may somehow modulate HH signaling. It is also possible that NRP interactions with other TM proteins, such as VEGF receptors, Plexins, FGF receptors, or PDGF receptors, may contribute to HH signal promotion (67,81), although many of these receptors interact with NRP1 through its extracellular domain, which, as our data indicate, is dispensable for NRP1 function in HH signaling. This contrasts with the extracellular domain, which is required for Semaphorin signaling, and a conserved SEA motif that is required for VEGF signaling.…”
Section: Identification Of a Cytoplasmic Motif In Nrp1 That Mediates mentioning
confidence: 75%
“…NRP1 is capable of binding to a broad repertoire of ligands, accounting for its diverse biological functions. First identified as the coreceptor for the secreted class III Semaphorins, such as Semaphorin 3A (Sema3A), 51 NRP1 was later shown to bind to a variety of growth factors, most notably VEGF 165 , as well as others including transforming growth factor beta, 52 53 platelet-derived growth factors C and D, 54 55 and c-Met. 56 Interestingly, recent studies have revealed that NRP1 also binds to extracellular microRNA/AGO2 complexes and facilitates their internalization, 57 adding another mechanism by which NRP1 modulates cellular functions.…”
Section: Introductionmentioning
confidence: 99%
“…Nrp1 is a co-receptor for multiple secreted factors such as semaphorins [ 14 ], VEGF-A [ 15 ], HGF [ 16 ], Hedgehogs [ 17 ], EGF [ 18 ], and PDGFBB [ 19 ] and TGFβs [ 20 ]. Due to its numerous co-receptor roles, Nrp1 participates in pleiotropic functions in many organs in a cell type-selective manner to modulate proliferation, migration, and survival.…”
Section: Introductionmentioning
confidence: 99%